(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
La copia livornese della princeps del Discorso sul testo della Commedia di Dante di Foscolo è un caso esemplare di volume postillato dallo stesso autore. Il saggio propone un primo esame delle postille in esso contenute e delle soluzioni editoriali adottate nell’Edizione Nazionale. Si concentra quindi sul commento di una postilla autografa che offre nuovi spunti interpretativi sulla concezione foscoliana di Dante riformatore religioso e sui rapporti del poeta con la comunità quacchera negli ultimi anni del suo soggiorno londinese. Notes on the glosses of Foscolo’s "Discourse on the text of Dante’s Comedy" and commentary on a ’quaker’ note The Livorno copy of the princeps of Foscolo’s Discorso sul testo della Commedia di Dante is a paradigmatic case of a volume glossed by the author himself. The present work aims at providing a first analysis of the said glosses and of the editorial solutions adopted in the Edizione Nazionale. In particular, the study focuses on the comment of an autograph gloss that may bring new insight into Foscolo’s idea of Dante as religious reformer and into the relationship between the late Foscolo and the Quaker community during the poet’s final years in London.